Alarmins HMGB1, IL-33, S100A7, and S100A12 in Psoriasis Vulgaris - Pavel Borsky; Zdenek Fiala; Ctirad Andrys; Martin Beranek; Kvetoslava Hamakova; Andrea Malkova; Tereza Svadlakova; Jan Krejsek; Vladimir Palicka; Lenka Borska; Vit Rehacek (Mediators of Inflammation)
Background. Psoriasis vulgaris is a chronic autoimmune disease associated with systemic inflammation. Increased levels of numerous cytokines, chemokines, growth factors, and other molecules were found in the skin and in the circulation of psoriatic patients. Alarmins, also known as danger signals, are intracellular proteins, which are released to an extracellular space after infection or damage. They are the markers of cell destructive processes. Objective. The aim of the present study was to evaluate the suitability of selected alarmins (HMGB1, IL-33, S100A7, and S100A12) as potential biomarkers of severity of psoriasis and to explore possible relationships between these proteins for the purpose of better understanding their roles in the immunopathology of psoriasis. Methods. The serum levels of selected alarmins were measured in 63 psoriatic patients and 95 control individuals. The levels were assessed by the ELISA technique using commercial kits. The data were statistically processed with MedCalc version 19.0.5. Results. In psoriatic patients, we found significantly increased levels of HMGB1 (p<0.05), IL-33 (p<0.01), S100A7 (p<0.0001), and S100A12 (p<0.0001). In addition, we found a significant relationship between HMGB1 and S100A7 (Spearman’s rho=0.276, p<0.05) in the patients and significant relationship between HMGB1 and IL-33 in the controls (Spearman’s rho=0.416, p<0.05). We did not find any relationship between observed alarmins and the disease severity. Conclusions. The alarmins HMGB1, IL-33, S100A7, and S100A12 were significantly elevated in the serum of patients, which states the hypothesis that they play specific roles in the immunopathology of psoriasis. However, we have not yet found a relationship between observed alarmins and the disease severity. The discovery of the relationship between HMGB1 and S100A7 is a novelty that should be studied in the future to further clarify its role and importance.